Bright Luminescence by Combining Chiral [2.2]Paracyclophane with a Boron–Nitrogen‐Doped Polyaromatic Hydrocarbon Building Block. Issue 11 (20th January 2022) - Rapp, Mario R.; Leis, Wolfgang; Zinna, Francesco; Di Bari, Lorenzo; Arnold, Tamara; Speiser, Bernd; Seitz, Michael; Bettinger, Holger F.
Abstract: Novel BN‐doped compounds based on chiral, tetrasubstituted [2.2]paracyclophane and NBN‐benzo[ f, g ]tetracene were synthesized by Sonogashira–Hagihara coupling. Conjugated ethynyl linkers allow electronic communication between the π‐electron systems through‐bond, whereas through‐space interactions are provided by strong π–π overlap between the pairs of NBN‐building blocks. Excellent optical and chiroptical properties in racemic and enantiopure conditions were measured, with molar absorption coefficients up to ϵ =2.04×10 5  M −1  cm −1, fluorescence quantum yields up to Φ PL =0.70, and intense, mirror‐image electronic circular dichroism and circularly polarized luminescence signals of the magnitude of 10 −3 for the absorption and luminescence dissymmetry factors. Computed g lum, calcd. values match the experimental ones. Electroanalytical data show both oxidation and reduction of the ethynyl‐linked tetra‐NBN‐substituted paracyclophane, with an overlap of two redox processes for oxidation leading to a diradical dication. Abstract : Coupling through‐bond and through‐space by a chiral building block results in excellent optical and chiroptical properties: ϵ up to 2.04×10 5  M −1  cm −1, Φ PL up to 0.70, and intense, mirror‐image electronic circular dichroism and circularly polarized luminescence (CPL) signals of a magnitude of 10 −3 for the absorption and luminescence dissymmetry factors.